Faktor-Faktor yang Memengaruhi Kinerja Perawat di Rumah Sakit: Literature Review - Alin, Dhemes; Adhani, Rosihan; Aflanie, Iwan; Herawati (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2024)
Objective: to identify factors that influence the performance of nurses in hospitals, including the application of Professional Nursing Care Methods (MAKP), career path development, and increased competency, which contribute to nurse performance so that the quality of hospital services is more optimal. Method: The method was searching three databases: Pubmed, Google Scholar, and Science Direct, with 7,821 articles. Search results using keywords obtained 20 articles, which were then selected and adjusted to an assessment based on full text, resulting in 9 articles. Results: Literature results show that the application of professional nursing care methods, clear career paths, and adequate competencies have a significant influence on nurse performance. These factors contribute to improving nurse performance. Conclusion: Nurse performance is influenced by various factors, including professional nursing care methods, career level, and competency. The application and development of these factors can have an impact on better and more optimal hospital services